The Impact of Fuel Price Changes on the consumer Price Index of Luang Prabang Province - SAVABOUTH, Khamlar; SIPHANTHONG, Bounthavy; SENGDARA, Chansamone; SIOUDOMPHAN, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The research on the impact of fuel price changes on the consumer price index of Luang Prabang province this time has brought the data gathered to summarize, interpret, consider, select, and analyze the estimated statistics to find the percentage value, the parameter value of the regression line equation with the long-term relationship model (Cointegration) with the method of Johansen and Juselius, and analyze the relationship in the short-term equilibrium point (Error Correction Model: ECM) of the fuel price change with the consumer price index through the E-view 10 program. The results of the research found: The correlation coefficient in the form of Correlation Matrix of the independent variable with the variable that is the price of oil and the consumer price index of LuangPrabang province is more than 0.8 or 80% with a confidence level of 95% and 99%, which means that the factors that the study team included in the model to analyze the relationship between the fuel price and the consumer price index are reliable. Therefore, through checking the properties of the model, it was found that the coefficient of decision Adjusted R-Square = 0.8186 which means that the independent variable fuel price change can explain the variable according to the consumer price index determined in the long term up to 81.86%, the rest depends on other factors that are not included in the study. Therefore, the model for analyzing the relationship between fuel price changes and the consumer price index in Luang Prabang province can be used and depends on at least one identified factor. Also, by bringing the data to test the effect of the independent variable on the variable in the short term (adjustment from the short-term equilibrium point to the long-term), ECM (-1) found that the analysis model of the effect of fuel price changes on the consumer price index in Luang Prabang province in the short term is not applicable and does not depend on the identified factors. But it will have a long-term effect, and checking the properties of the model found that the coefficient of decision Adjusted R-Square = 0.0268, which means that the independent variable fuel price change can explain the change according to the consumer price index determined in the short term by only 2.68%, so it can be said that the change in fuel price in the short term does not affect the consumer price index in Luang Prabang province, but the change in fuel price in the long term will affect the consumer price index in Luang Prabang province.